3D inductive power transfer power system. Issue 1 (March 2014) - Raval, Pratik; Kacprzak, Dariusz; Hu, Aiguo P.
<x content-type="archive" xml:space="preserve">Abstract</x> To date, the technique of inductive power transfer has found applications in industry including two-dimensional battery charging. However, this restricts any load to planar movements. This paper proposes custom designed magnetic structures of a loosely magnetically coupled three-dimensional inductive power transfer system. This is done via computational software utilizing the finite-element-method. More specifically, single-phase and multi-phase primary magnetic structures are proposed to distribute a power transfer window along three orthogonal axes. Next, a secondary magnetic structure is custom designed to induce electromotive force in three-dimensions. The proposed system is simulated to demonstrate power transfer for charging an AA-battery cell. Finally, the thermal effects upon the secondary load are considered.